Protein denaturation in pilot scale spray dryer - Kioh, Shin Fang (2010)
The aim of this project is to investigate the protein denaturation in a pilot scale spray dryer. The occurrence of protein denaturation is due to external stresses, such as heat. Thus, this project describes a pilot process for obtaining protein isolates from whey protein in powder form via spray drying process with improved water solubility and technofunctional properties as well as reduced thermal damage. The experiment, including varying the inlet air temperature at 100°C and 160°C as well as utilising the microencapsulation technique using a starch derived polysaccharide (or known as maltodextrin) to minimize the protein denaturation. The Reversed phase HPLC (RP-I-IPLC) technique has been applied to measure the denaturation of proteins in the samples which are with maltodextrin and without maltodextrin resulting from the spray drying of milk solution at inlet temperature of 100°C and 160°C. The combination of maltodextrin (MD) and fresh milk (FM) is at standard ratio of FM/MD (9: 1) in order to produce spherical and smooth powder. Apart from the RP-HPLC method, the SDS-PAGE method also used to analyze the protein content. The morphology of the milk powders was examined using a Scanning Electron Microscopy (SEM) while the particle size of milk products can be easily assessed using Mastersizer with model Scirocco 2000. To determine the portion of whey protein in the spray dried milk samples, the Total Solid Content method was employed. Besides, sterilization tests such as detection of Salmonella sp., and detection of Escherichia coli sp. along with microbial tests which is Standard Plate Count Method also applied. The spray-drying process was particularly critical for inducing some thermal damage but it is hypothesized that the crust formation which resulting in high particle temperatures while still maintaining a wet core, is likely to lead to high levels of denaturation up to 55% at high temperature (160 °C). Stability of a-lactalbumin proved higher as compare with fl-lactoglobulin. The study reveals that low outlet gas temperatures along with microencapsulation are required to avoid excessive denaturation of protein which can reduce the protein denaturation until 16%. Up to 93.2% reduction of the microorganisms also proved that spray drying is another form of sterilization.